Proceso evolutivo de la lógica de la deducción hacia la probabilidad aplicada a la educación. - Cárdenas Criollo, Mishel Alexandra (2018)
The educational process required to give greater emphasis in structuring of strategies for inductive processes that determine significance of learning since knowledge of probability helps teachers manage different realities of the field of education and learning processes of each student, to comply with the criterion of performance set for the class. On the basis of the above before taking into account the need to analyse the structure of logic of chance through a relevant bibliographical and historical inquiry that also provide a critical approach to demonstrate that inclusion application of inductive logic in the learning process is necessary and positive. In accordance with the work carried out was obtained as main finding and conclusion, to know that probability has the proposition raised by first order logic, because of subjectivity which is expressed and which gives infinity as fundamental structure of responses to the same topic. This subjective expression serves to the exercise of a conditional probability which is expressed by Bayes’s theorem, which considers that the hypothesis or prior knowledge, allows to know probability of answers to certain variations of the constant or in this case the educational reality that faces a constant problem, that is the application of teaching strategies in different groups of students.